Kesan Projek Lebuhraya Pan Borneo Terhadap Masyarakat Setempat - Maiman, Micklyn Jeavon Bin; Ahmad Latiffi, Aryani (Research in Management of Technology and Business, 2023)
Various implementations of highway development are carried out to improve the transport system in the country, especially in rural areas. The Pan Borneo Highway is one of Malaysia's mega projects to further improve the quality of existing roads to a better and more efficient highway. Nevertheless, this project has directly and indirectly created various impacts on the local population in the construction area of the Pan Borneo Highway, which is packed into WPC10 which is 30 kilometers (km) long. Therefore, this study was conducted to identify the impact of the construction of the Pan Borneo Highway on the local population and the measures taken by relevant parties to address the impact of the construction of the Pan Borneo Highway on the local population. A qualitative method was used to gain answers to the research questions. Semi-structured interviews were conducted with the local community consisting of Village Heads, Village Development and Security Committees (JKKK), university students, fishermen and engineers from the Project Implementation Partner (PDP) involved in the construction of the Pan Borneo Highway. Based on the results of the interviews, the impact of the construction of the Pan Borneo Highway on the socioeconomics of the local community, namely the improvement of infrastructure, increased job opportunities and the loss of land and livelihoods of the community has occurred in the study area (WPC10) Furthermore, actions that can be taken to overcome the impact is the provision of compensation, maintenance and provision of road safety. In conclusion, the information from this study can help all parties either academically or in the construction sector provide clear information about the impact of the construction of the Pan Borneo Highway on the local community and actions that can be taken by relevant parties to overcome it.